ChemInform Abstract: Bis‐Functionalization of 1, 3‐Dienes Through 1, 4‐Conjugate Addition of Amphiphilic Bis‐π‐Allyl and Related Palladium Intermediates. Issue 30 (29th July 2014) - Baiju, T. V.; Vijayan, Ajesh; Joseph, Nayana; Preethalayam, Preethanuj; Radhakrishnan, K. V.; Suresh, E.; Yamamoto, Yoshinori
Abstract Bis‐allylation of functionalized 1, 3‐dienes is achieved via Pd‐catalyzed coupling with allyl stannane and allyl chloride.